Electrophoretic (Infiltration) Deposition of Thick Conductive Fiber Preforms. Issue 11 (1st January 2015) - Iveković, A.; Novak, S.
Abstract : Relevant conditions for electrophoretic (infiltration) deposition (EPID) of thick conductive fiber preforms were investigated. Modified electrophoretic deposition cell was used to fabricate conductive fiber-reinforced composites from an aqueous suspension. Infiltration of conductive preforms proceeds in a similar manner as for non-conductive fiber reinforcements, by deposition at the electrode and backfilling of the fiber preform.